Law Enforcement Against Street Crimes During a Pandemic That Occurred In Sidoarjo - Agung Kurniawan; Bastianto Nugroho (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The purpose of this research is Law Enforcement Efforts Against Street Crime Period in Sidoarjo. The research method used is a normative juridical research method, which focuses on the study starting from the provisions of the applicable laws and regulations, accompanied by legal theories and principles related to the problems studied. The results of the research In carrying out the prevention of street crime, the Sidoarjo City Police made several efforts, namely with Preventive Efforts and Repressive Efforts. The efforts to overcome street crime are carried out by carrying out patrols carried out by the police, the establishment of Tangguh village posts spread across almost all areas from the RT, RW and Village levels, empowerment of Bhabinkamtibmas, involvement of elements related to handling the pandemic (TNI, Regional Government, BPBD), carry out operations to control the completeness of motorized vehicles, with the application the community can easily communicate with the police, and also the police give mandate to the community if a crime occurs so that they can immediately report it to the authorities. And there are also obstacles What is often encountered by the Sidoarjo City Police is that the public does not understand the dangers of the Covid 19 pandemic and its impact on the increase in crime, by ignoring health protocols and decreasing the level of vigilance for the occurrence of crime. The public's rejection of the efforts / policies taken by the government related to the handling of the Covid 19 Pandemic on the grounds that these policies limit the space for people to find sustenance, as well as the limited number of personnel and finances for the deployment of a humanitarian operation.